1989
DOI: 10.1007/bf01795360
|View full text |Cite
|
Sign up to set email alerts
|

MEIC—A new international multicenter project to evaluate the relevance to human toxicity of in vitro cytotoxicity tests

Abstract: A new international project to evaluate the relevance for human systemic and local toxicity of in vitro tests of general toxicity of chemicals has been organized by the Scandinavian Society of Cell Toxicology under the title Multicenter Evaluation of In Vitro Cytotoxicity (MEIC). The basic assumptions underlying the project, as well as the practical goals and the design of the program are outlined. The list of the first 50 reference chemicals is presented. The chemicals are an otherwise unbiased selection of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 173 publications
(48 citation statements)
references
References 24 publications
(27 reference statements)
0
48
0
Order By: Relevance
“…Because the ATP assay is often used to evaluate cytotoxicity in an in vitro mammalian cell genotoxicity test, 12 of the compounds used in this study were those reported by Matsushima et al (1999) to possess various genotoxic properties. In addition, 7 compounds were selected from a report that established drug cytotoxicity (Evans et al, 2001), and 5 compounds were selected from a report based on a multicenter evaluation of in vitro cytotoxicity (MEIC) (Bondesson et al, 1989). Because sensitivity to cytotoxicity may be changed by cell density, we confirmed that the doubling time of the control cells corresponds to the logarithmic growth phase of CHL cells during drug treatment in this experiment.…”
Section: Discussionmentioning
confidence: 58%
“…Because the ATP assay is often used to evaluate cytotoxicity in an in vitro mammalian cell genotoxicity test, 12 of the compounds used in this study were those reported by Matsushima et al (1999) to possess various genotoxic properties. In addition, 7 compounds were selected from a report that established drug cytotoxicity (Evans et al, 2001), and 5 compounds were selected from a report based on a multicenter evaluation of in vitro cytotoxicity (MEIC) (Bondesson et al, 1989). Because sensitivity to cytotoxicity may be changed by cell density, we confirmed that the doubling time of the control cells corresponds to the logarithmic growth phase of CHL cells during drug treatment in this experiment.…”
Section: Discussionmentioning
confidence: 58%
“…A 7-year, international, multicenter study (MEIC) involving 29 laboratories and 61 different cytotoxicity assays evaluated the relevance of in vitro cytotoxicity testing in numerous cell types in relation to in vivo human toxicity [18]. Fifty chemicals were studied, including poisons, prescription drugs, substances of abuse, and common household chemicals.…”
Section: In Vitro Cytotoxicity and Predicting Drug Attritionmentioning
confidence: 99%
“…The second mission was concretized in the form of the Multicentre Evaluation of In vitro Cytotoxicity (MEIC) programme, directed at an evaluation of the predictive value for human toxicity of in vitro cytotoxicity tests. The study was launched in 1989 [6] and completed in 1999 [7].…”
Section: The Societymentioning
confidence: 99%